Invasive streptococcal disease: a review for clinicians. Issue 1 (25th July 2015) - Parks, Tom; Barrett, Lucinda; Jones, Nicola
Abstract : Introduction: Streptococci are a genus of Gram-positive bacteria which cause diverse human diseases. Many of these species have the potential to cause invasive infection resulting from the presence of bacteria in a normally sterile site. Sources of data: Original articles, reviews and guidelines. Areas of agreement: Invasive infection by a streptococcus species usually causes life-threatening illness. When measured in terms of deaths, disability and cost, these infections remain an important threat to health in the UK. Overall they are becoming more frequent among the elderly and those with underlying chronic illness. New observational evidence has become available to support the use of clindamycin and intravenous immunoglobulin in invasive Group A streptococcal disease. Areas of controversy: Few interventions for the treatment and prevention of these infections have undergone rigorous evaluation in clinical trials. For example, the role of preventative strategies such as screening of pregnant women to prevent neonatal invasive Group B streptococcal disease needs to be clarified. Future prospects: Studies of invasive streptococcal disease are challenging to undertake, not least because individual hospitals treat relatively few confirmed cases. Instead clinicians and scientists must work together to build national and international networks with the aim of developing a more complete evidence base for the treatment and prevention of these devastating infections.